Metastatic Carcinoma of Unknown Primary Presenting as Jugular Venous Thrombosis - Prince Cheriyan Modayil; Sathyan Panthakalam; David C. Howlett (Case Reports in Medicine)
Jugular venous thrombosis is unusual and is associated with central venous catheterisation, intravenous drug abuse and head and neck sepsis. It is rarely associated with malignancy. We report a case of metastatic carcinoma of unknown primary in a forty year old female which presented with jugular venous thrombosis. The discussion includes investigation and treatment options for this condition.